Economics of Industrial Plantation of Bambusa arundinacea by Underplanting - Bhat, A. S. (Indian Forester, 1970)
Development of forests for industrial purposes, was one of the objects enunciated by the Government of India under the "National Forest Policy Resolution, 1952". Although of late attempts are indeed being made by a few State Governments in this direction, these are far too inadequate to keep pace with the increasing industrial demands. Bamboo, the major long fibred raw material resource for the pulp industry in India, is fast becoming scarce, and as a result, for its collection the Mills often cover, uneconomically long distances adding up to the cost of production of pulp which is considered already too high as compared with the international standards. The raw material requirement of the pulp industry which is about 2.4 million tons per year at present is expected to gradually shoot up to 10 million tons by 1980-81. As against this, it is estimated, that the natural bamboos from the forests, even after judicious management, are not likely to provide more than 2 million tons annually. The magnitude of the problem confronting the pulp industry is thus quite apparent, and unless effective measures are taken up, the industry is destined to stagnate. It is inconceivable that the Government alone would be able to do much in solving this vital problem of raw material scarcity. The situation, therefore, demands co-ordinated efforts both by the industry and the Government to supplement the natural raw material resources, by raising plantations of fast growing pulpable species like the bamboo. Land, Capital, Skill and Labour are the basic requirements for raising a plantation. Although skill and Labour may be presumed to be readily available, the position regarding the Land and Capital needs further investigation.